2021
DOI: 10.1186/s12891-021-04193-w
|View full text |Cite
|
Sign up to set email alerts
|

Radiological tarsal bone morphology in adolescent age of congenital clubfeet treated with the Ponseti method

Abstract: Background Major abnormalities of tarsal bone shape after surgical clubfoot treatment are well known from the literature. The Ponseti method has gained widespread acceptance in primary treatment of congenital clubfeet. Despite the longtime experience, data regarding the development of tarsal bones after this treatment are still rare. The aim of the study was therefore to evaluate radiographic parameters describing tarsal bone shape of clubfeet after Ponseti treatment and compare them to age-mat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…Two studies describe in detail the radiological morphology of the talus in treated clubfeet. Hamel et al [17] found the most consistent difference compared to controls was the previously described loss of dorsal talar neck depth, which they refer to as the 'anterior motion segment'. An MRI study by Feng et al [18] corroborates this, showing that the depth of the 'talar groove' was on average 2 mm less in clubfeet than in controls.…”
Section: Pathoanatomymentioning
confidence: 87%
See 3 more Smart Citations
“…Two studies describe in detail the radiological morphology of the talus in treated clubfeet. Hamel et al [17] found the most consistent difference compared to controls was the previously described loss of dorsal talar neck depth, which they refer to as the 'anterior motion segment'. An MRI study by Feng et al [18] corroborates this, showing that the depth of the 'talar groove' was on average 2 mm less in clubfeet than in controls.…”
Section: Pathoanatomymentioning
confidence: 87%
“…Hamel et al . [17] found the most consistent difference compared to controls was the previously described loss of dorsal talar neck depth, which they refer to as the ‘anterior motion segment’. An MRI study by Feng et al .…”
Section: Introductionmentioning
confidence: 90%
See 2 more Smart Citations
“…The FPS validation paper has been further cited in outcome-based studies (26,33) and in a systematic review of assessing foot-types (34). The study analysing foot function and perceived outcomes in symptomatic clubfoot has been cited in review papers of clubfoot management (35,36) and outcome-based studies (26,37).…”
Section: Discussionmentioning
confidence: 99%